Efficacy and safety of Iguratimod in the treatment of Ankylosing Spondylitis: A systematic review and meta-analysis of randomized controlled trials - Long, Zhiyong; Deng, Ying; He, Qi; Yang, Kailin; Zeng, Liuting; Hao, Wensa; Deng, Yuxuan; Fan, Jiapeng; Chen, Hua (Frontiers in Immunology, 2023)
Objective: To explore the efficacy and safety of Iguratimod (IGU) intervention in the treatment of Ankylosing Spondylitis (AS). Methods: We used computer to search literature databases, collected randomized controlled trials (RCTs) related to IGU treatment of AS, and searched the relevant literature in each database until Sep. 2021. Two researchers independently carried out literature screening, data extraction, and evaluation and analysis of the risk of bias in the included studies, and then used Rev Man5.3 software for meta-analysis. The protocol is CRD42020220798. Results: A total of 9 RCTs involves in 553 patients were collected. The statistical analysis showed that IGU can decrease the BASDAI score (SMD -1.62 [-2.20, -1.05], P<0.00001. Quality of evidence: low), the BASFI score (WMD -1.07 [-1.39, -0.75], P<0.00001. Quality of evidence: low) and the VAS (WMD -2.01 [-2.83, -1.19], P<0.00001. Quality of evidence: very low). Meanwhile, the addition of IGU into the conventional therapy would not increase the adverse events (RR 0.72 [0.47, 1.12], P=0.15. Quality of evidence: moderate). Conclusion: IGU may be an effective and safe intervention for AS.